World Congress on Medical Physics and Biomedical Engineering 2018 June 3-8, 2018, Prague, Czech Republic (Vol.1) - Lhotska, Lenka; Sukupova, Lucie; Lacković, Igor.; Ibbott, Geoffrey S.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents the proceedings of the IUPESM World Congress on Biomedical Engineering and Medical Physics, a tri-annual high-level policy meeting dedicated exclusively to furthering the role of biomedical engineering and medical physics in medicine. The book offers papers about emerging issues related to the development and sustainability of the role and impact of medical physicists and biomedical engineers in medicine and healthcare. It provides a unique and important forum to secure a coordinated, multileveled global response to the need, demand, and importance of creating and supporting strong academic and clinical teams of biomedical engineers and medical physicists for the benefit of human health. Chapter "Evaluation of the Impact of an International Master of Advanced Studies in Medical Physics" is available open access under a Creative Commons Attribution 3.0 IGO Licence via link.springer.com.
Diagnostic Imaging -- Image Processing -- Information Technology in Healthcare -- Modelling and Simulation -- BME and MP Education, Training and Professional Development -- Patient Safety -- Accreditation and Certification -- Health Technology Assessment -- Biosignals Processing -- Biomechanics, Rehabilitation and Prosthetics -- Minimum Invasive Surgery, Robotics, Image Guided Therapies, Endoscopy -- Diagnostic and Therapeutic Instrumentation -- Micro- and Nanosystems, Active Implants, Biosensors -- Neuroengineering, Neural Systems -- Biomaterials, Cellular and Tissue Engineering, Artificial Organs -- Assistive Technologies -- Biological Effects of Electromagnetic Fields -- Clinical Engineering -- Radiation Oncology Physics and Systems -- Dosimetry and Radiation Protection -- Advanced Technologies in Cancer Research and Treatment -- Biological Effects of Ionizing Radiation -- Nuclear Medicine and Molecular Imaging.
Keywords: Biomedical engineering; Medical physics; Biomaterials; Computer vision; Biomedical Engineering and Bioengineering; Medical Physics; Biomaterials; Computer Vision